Removal of Heavy Metals from Synthetic Landfill Leachate Using Oyster Shells Adsorbent - Song, Tie-Hong; Gao, Yan-Jiao (Asian Journal of Chemistry, 2013)
This paper investigated the adsorption capacities of crushed oyster shells- adsorbent for removal of several heavy metal ions from synthetic landfill leachate using batch experiments. Adsorbent characterization, single-constituents metal ion adsorption kinetics, single metal adsorption equilibrium isotherm models were assessed. The results showed that: a 24 h period was considered to provide an adequate contact time between the single-constituent metal ion solutions and the adsorbent to reach equilibrium; the equilibrium adsorption capacities of the adsorbent for single-constituent metal ion solutions was noted to be Cd > Co > Ni > Mn; after a 24 h contact period with crushed oyster shells, the solution pH was generally found to equilibrate at approximately pH of 8. The metal adsorption capacities generally increased with increasing initial metal concentration and decreased when adsorbent masses were increased in solution; the Langmuir model was found to provide a better fit to the experimental equilibrium data of nickel adsorption.